TINDAKAN MEDIS EUTHANASIA DALAM PERSPEKTIF PENDIDIKAN HUKUM ISLAM - fatri sagita (IAI DDI Polewali Mandar, 2019)
The purpose of this study are: 1) to know the actions of a doctor in dealing with euthanasia problems from the perspective of Islamic criminal law; and 2) knowing the actions of a doctor in dealing with euthanasia issues in terms of Human Rights. The results showed that the actions of a doctor in dealing with euthanasia problems from the perspective of criminal acts of Islamic law, especially euthanasia is actively forbidden because it is categorized as an act of suicide that is forbidden and threatened by Allah SWT with the punishment of hell forever, because the right to end one's life is God SWT. Therefore, the person who ends his life or the person who helps in this case a doctor who speeds up a person's death is tantamount to opposing the provisions of Islam.